Blake's Heavy Metal: The History, Weight, Uses, Cost, and Makers of His Copper Plates. - Bentley, G. E. (University of Toronto Quarterly)
This article describes the materials the poet William Blake used in creating his copper plates for "Songs of Innocence and of Experience," "America," "Europe," "For the Sexes: The Gates of Paradise," and "Jerusalem." The article discusses who made the copper plates, how they were used, the printing process and the cost to Blake, as well as why they are now largely lost.